Analisis Potensi Tumbuhan Lokal Untuk Meremediasi Limbah Logam Berat Timbal (Pb) Sekitar Lahan Bekas Penambangan Emas Tanpa Izin (PETI) Di Desa Moenti Kabupaten Sarolangun Provinsi Jambi - Zuli Rodhiyah; Andika Rizki Mulia; Freddy Ilfan; Mahya Ihsan (Universitas Batanghari Jambi, 2023)
Illegal gold mining is gold mining activity carried out by gold miners who do not have legal mining permits. The process of illegal gold mining is carried out by the community using a diesel-fueled suction machine, which can cause the air to be polluted by lead so that it pollutes the soil through sedimentation and precipitation processes and must be given treatment to reduce the levels of heavy metals in the soil. The purpose of this study was to analyze local plants that are able to absorb the heavy metal lead (Pb) in the soil. The results of the analysis in this study identified 14 local plant species found in the research location. The three plants with the highest Important Value Indeks (INP) were Phragmites sp. with an INP value of 37.35%, Melastoma sp. with an INP value of 30.64%, and Eleocharis interstincta with an INP value of 25.41%. The highest Pb concentration in the soil was 0.533 mg/kg and the lowest was 0.452 mg/kg. The Pb concentration in the shoots of Eleocharis interstincta was 0.156 mg/kg, in the shoots of Phragmites sp. was 0.106 mg/kg, and in the shoots of Melastoma sp. was 0.074 mg/kg. The Pb concentration in the roots of Eleocharis interstincta was 0.258 mg/kg, the roots of Phragmites sp. 0.309 mg/kg, and the roots of Melastoma sp. 0.162 mg/kg. The BAC, BCF, and TF values of these three plants were 1, which indicated that these three plants were not in the phyto-extractor plant category but were included in the phytostabilization category.